Feeding practice of infant and young children and their nutritional status among tea worker community of West Tripura district, India: an observational study - Saha, Arjun; Bhattacharjya, Himadri (International Journal Of Community Medicine And Public Health, 2018)
Background: People working in tea gardens of Tripura differ from other people in terms of ethnicity, culture, food habit, literacy etc. and limited information is available regarding infant feeding practices and its association if any, with nutritional status of under-five children of this community. Methods: This community based cross-sectional study was conducted during 1st July to 31st August 2016, using a validated interview schedule, among 170 women working in different tea estates of West Tripura district, having children aged 6 months to 2 yr, chosen by multistage sampling. Descriptive statistics and χ2 test were used to present data. P value ≤0.05 was considered statistically significant. Results: Breastfeeding initiation rate within one hr of birth was 50.59%, colostrums was fed to 82.35%, prelacteal feeding was given to 30.59%, 65.88% were exclusively breast fed and overall feeding practice was proper in 51.76% of the study children. Khichdi (34.1%) was the commonest complimentary feed and katori and spoon (64.7%) were the commonest feeding utensils. Prevalence of underweight, stunting and wasting was 9.0%, 12.9% and 7.3% respectively and these were found to be more frequent among children who received prelacteal feeding, late initiation of breastfeeding and early complimentary feeding, though statistically these were not significant. Conclusions: Overall infant feeding practice was better among educated mothers and institutional births; hence improvement in literacy and promoting institutional deliveries will further improve feeding practice in this community. Though underweight, stunting and wasting was prevalent but these had no significant association with feeding practices. Hence further studies are required to investigate the causes of malnutrition among children of this community.